Conventional versus Instillation Negative-Pressure Wound Therapy for Severe Soft Tissue Injury in Open Pelvic Fractures: A Retrospective Review - Choi, Donghwan; Cho, Won Tae; Song, Hyung Keun; Kwon, Junsik; Kang, Byung Hee; Jung, Hohyung; Kim, Min Ji; Jung, Kyoungwon (Yonsei medical journal, 2025)
We investigated the clinical features, current negative-pressure wound therapy (NPWT) management strategies, and outcomes of pelvic-perineal soft tissue infection after open pelvic fractures. We analyzed the data of patients admitted to our trauma center with pelvic-perineal soft tissue after open pelvic fractures over a 7-year period. We investigated the injury severity score (ISS), medical costs, number of NPWTs, time required to reach definite wound coverage, complications, fracture classifications, transfusion requirements, interventions, length of stay (LOS) in hospital and intensive care unit (ICU), and prognosis. Twenty patients with open pelvic fractures were treated with NPWT, and one patient who underwent NPWT died of pelvic sepsis during ICU treatment. The median LOS in hospital and medical costs were 98 [56-164] days and 106400 [65600-171100] USD, respectively. Patients treated with instillation NPWT (iNPWT, n=10) had a shorter NPWT duration (24 [13-39] vs. 46 [42-91] days, =0.023), time to definite wound coverage (30 [21-43] vs. 49 [42-93] days, =0.026), and hospital LOS (56 [43-72] vs. 158 [101-192] days, =0.001), as well as lower medical costs (67800 [42500-102500] vs. 144200 [110400-236000] USD, =0.009) compared to those treated with conventional NPWT. NPWT is a feasible method for treating pelvic soft tissue infections in patients with open pelvic fractures. iNPWT can reduce the duration of NPWT, hospital LOS, and medical costs.